A urbanização do bairro Valentina Figueiredo e suas desigualdades sociais. - Silva, Eron Carlos Santos da. (2014)
The Brazilian urban expansion happened mainly from the 1940s, we can consider this decade as a landmark due to outflow of population from rural areas to the cities with population growth provided a rapid increase in the urban population.This phenomenon was not isolated in the Brazilian industrial cities, reaching small towns as was the case of João Pessoa-PB. This rapid growth brought a worsening housing problems and creating social tensions in the city, so many of those who came to the city had not nowhere to live.This work targets the urban sprawl and changes in the form of land use atValentinaFigueiredo, located in the south of the city of João Pessoa-PB. During its execution was made works on the site of the study to assess their current situation and research about his foundation. It was found that the group had been founded to meet the existing housing deficit in John person the time of its founding and today still has an important role in this regard, in order to be one of the few possibilities for horizontal growth of the city of João Pessoa, east is bordered by the Atlantic Ocean, the north is troubled with the municipality of Cabedelo and the west with the municipality of Bayeux. We note thatValentinaFigueiredo undergoes structural and social changes which is a reflection of population growth in the city of João Pessoa.